2013
DOI: 10.1371/journal.pone.0072041
|View full text |Cite
|
Sign up to set email alerts
|

Difference in Visual Processing Assessed by Eye Vergence Movements

Abstract: Orienting visual attention is closely linked to the oculomotor system. For example, a shift of attention is usually followed by a saccadic eye movement and can be revealed by micro saccades. Recently we reported a novel role of another type of eye movement, namely eye vergence, in orienting visual attention. Shifts in visuospatial attention are characterized by the response modulation to a selected target. However, unlike (micro-) saccades, eye vergence movements do not carry spatial information (except for de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
2
19
0
Order By: Relevance
“…In the present study, we aimed to investigate whether individual perceptual styles selectively affect the aesthetic experience of ambiguous artworks with part-whole perceptual ambiguity (i.e., Arcimboldo's paintings) by biasing the orientation of visual attention (Solé Puig et al, 2013). Cupchik and colleagues (2009) showed that aesthetic experience arises from the interaction between top-down orienting of attention and bottom-up perceptual facilitation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, we aimed to investigate whether individual perceptual styles selectively affect the aesthetic experience of ambiguous artworks with part-whole perceptual ambiguity (i.e., Arcimboldo's paintings) by biasing the orientation of visual attention (Solé Puig et al, 2013). Cupchik and colleagues (2009) showed that aesthetic experience arises from the interaction between top-down orienting of attention and bottom-up perceptual facilitation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we hypothesized that individual perceptual style, which biases the orientation of visual attention (Solé Puig et al, 2013), leads to a preference for a particular level of a percept (i.e., global or local), and thus selectively affects the aesthetic pleasure of ambiguous artworks that show part-whole perceptual ambiguity (i.e., Arcimboldo's portraits). It has been suggested that perceiving ambiguity results in distributed microconsciousnesses for perceptual attributes (Zeki, 2004), in both time and space (Kleinschmidt et al, 1998).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Eye fixations were computed using Eyeworks (Eye Tracking Inc®, Sweden) and total number of fixations were calculated for each task. The criteria for counting a fixation was set to 250msec (5x5 pixel; [12,13]). …”
Section: Cognitive Workload (Cwl)mentioning
confidence: 99%